1992
DOI: 10.1127/agdonauforschung/8/1992/101
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological investigations in the river Danube: Measuring microbial activities and biomass

Abstract: Bacterial numbers, biomass and production estimates were performed in the impound ment of Altenworth (Austrian part of the Danube) and in a longitudinal profile of the Danube between stream kilometers 16 and 1934. For production estimates, two approaches were compared. The frequency of dividing cells (FDC) approach gave higher estimates compared with the thymidine incorporation approach. The two approaches showed no parallel results, FDC seems to reflect past activities of allochthonous bacteria in their indig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The predominance of small bacteria (0.24 pm3; Kasimir 1992) and a high flagellate abundance (mean: 4.6 X 103 ml-') in the River Danube support this conclusion. The flagellate abundance found in this study is in good agreement with that reported by Kasimir (1992) (range: 1 to 22 X 103 ml-l); similarly, Carlough & Meyer (1989) found l l X 103 flagellates ml-' in the Ogeechee River. Despite high flagellate numbers commonly occurring in rivers, Fenchel (1986) noted that protists are not important in lotic systems because of high wash-out rates.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…The predominance of small bacteria (0.24 pm3; Kasimir 1992) and a high flagellate abundance (mean: 4.6 X 103 ml-') in the River Danube support this conclusion. The flagellate abundance found in this study is in good agreement with that reported by Kasimir (1992) (range: 1 to 22 X 103 ml-l); similarly, Carlough & Meyer (1989) found l l X 103 flagellates ml-' in the Ogeechee River. Despite high flagellate numbers commonly occurring in rivers, Fenchel (1986) noted that protists are not important in lotic systems because of high wash-out rates.…”
supporting
confidence: 81%
“…During periods of tant abiotic factors regulating bacterial activity (via generally high remineralizatlon activity, the abunalteration of the amount of suspended and dissolved dance of more refractory compounds led to a lower organic matter), no correlation could be detected bepercentage of DOC being utilized by the bacterial tween BOD rates and discharge (Kasimir 1992). Fluctucommunity and hence to lower oxygen consumption in ations in suspended matter may influence other imporBODs.…”
mentioning
confidence: 92%
“…As observed by Grobois et al (2001), the downstream site remained the most productive zone of this stretch all along the sampling period, owing to the tributaries input. The bacterial density increased up-to downstream as observed in the Meuse (Servais, 1989) and in the Danube (Kasimir, 1992). At 4Ch, the very high numbers of bacteria, certainly supported by the carbon inputs of the tributaries, were in the upper range of the values observed in rivers (Servais,1989;Kasimir, 1992;Hoch et al, 1995;Basu & Pick, 1997;Meybeck et al, 1998).…”
Section: Water Composition and Potamoplanktonmentioning
confidence: 81%
“…Bacteria often show an affinity for flocs because of their protective support as a beneficial microhabitat and because organic nutrients adsorb onto particulate surfaces and thus represent a nutrient source and colonization site for the bacteria (Paerl, 1975;Goulder, 1976;Logan and Hunt, 1987). While attached bacteria may not always be dominant, the significance of this sediment-bacteria relationship lies in the fact that bacteria associated with particulate surfaces demonstrate greater metabolic activity than free-floating bacteria (Logan and Hunt, 1987;Kasimir, 1992). Liss et al (1996) have demonstrated that it is the bacteria's metabolic production of EPS which is the dominant mechanism controlling floc development, structure, stability, and behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…Bacteria have been shown to be an integral part of most natural floc structures (Logan and Hunt, 1987;Droppo and Ongley, 1989, 1992Muschenheim et al, 1989;Liss et al, 1996) and were observed to be an important constituent of MRD flocs for the September samples. While often the majority of bacteria are free-floating in freshwater environments (Geesey and Costerton, 1979;Kirchman, 1983), there are reports of environments and conditions where the attached bacteria are dominant (Goulder, 1976;Bell and Albright, 1981;Lind and Lind, 1991).…”
Section: Resultsmentioning
confidence: 99%